2021
DOI: 10.1111/eci.13671
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular ultrasound insights into the unstable features of the coronary atherosclerotic plaques: A systematic review and meta‐analysis

Abstract: Background: There is a lack of a comprehensive picture of plaque geometry and composition of unstable atherosclerotic lesions as observed with intravascular ultrasound techniques.We analysed through a systematic review with meta-analysis 39 characteristics of atherosclerotic plaques in three scenarios involving culprit and non-culprit lesions from acute coronary syndromes vs stable angina pectoris patients, and culprit vs nonculprit lesions in acute coronary syndromes patients. Methods: A systematic search of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…They coalesce into larger mases over time to form speckles, further progressing to calcified sheets or plates. Fragmentation of these sheets leads to nodules that may extend to the lumen and become protuberant with discontinuation of the endothelium [ 15 ]. Calcification of coronary arteries is an excellent predictor of atherosclerotic plaque burden and may contribute to atherosclerotic plaque rupture, though the connection between atherosclerotic plaque calcification plaque rupture is heavily debated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They coalesce into larger mases over time to form speckles, further progressing to calcified sheets or plates. Fragmentation of these sheets leads to nodules that may extend to the lumen and become protuberant with discontinuation of the endothelium [ 15 ]. Calcification of coronary arteries is an excellent predictor of atherosclerotic plaque burden and may contribute to atherosclerotic plaque rupture, though the connection between atherosclerotic plaque calcification plaque rupture is heavily debated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies show a link between high CAC and risk of cardiac events and mortality, yet some studies have suggested that the most calcified plaques may be more stable, and that the plaques most vulnerable to rupture may be those which have a mixed composition of calcified and uncalcified tissue [ 16 ]. Indeed, unstable lesions are associated with focal calcium deposits that may be related to fibrous cap disruption [ 15 ]. Calcium in a spotty distribution has previously been observed, pathologically, in sudden coronary death victims [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic manifestations of atherosclerosis vary in each individual and throughout the body; it is not fully understood why plaque formation has such a heterogeneous distribution, although different arterial systems are correlated [ 1 , 2 , 3 ]. Moreover, risk factors (such as diabetes mellitus, hypertension, smoking, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…OCT or Intravascular Ultrasound (IVUS) offers the third dimension to the coronary lumen and wall and, due to CA limitations and low sensitivity, is the only method for accurate SCAD diagnosis [ 8 , 9 , 27 , 28 , 29 , 30 ]. Both methods can provide the SCAD diagnosis, but OCT, due to its superior resolution in image acquisitions, is the method of choice [ 8 , 9 ].…”
Section: Spontaneous Coronary Artery Dissection (Scad)mentioning
confidence: 99%